Mobile app for the accuracy of emergency drug administration in children's cardiovascular resuscitation : A literature review - Sasongko, Arie; Purnawan, Iwan (Alma Ata University Press, 2023)
Background : Errors in the calculation of drug titration are one of the causes of medical errors that have an impact on the implementation of cardiopulmonary resuscitation in children. Calculations based on age, child weight and incorrect anthropometric data are what cause medical errors in the administration of emergency drugs in cases of pulmonary cardio resuscitation. One strategy in utilizing technological advances to minimize the occurrence of medical errors in drug administration with the titration method is to use a dose calculation application for drug titration.Objectives : The purpose of this literature review is to analyze the effect of using drug administration calculation applications for the prevention of medical errors in emergency cases and pediatric cardiopulmonary resuscitation. Methods : This research method is a literature review using PRISMA analysis with a database of PUBMED, Science Direct, Proquest, Springer, Wiley, Taylor ,and France from 2017-2022. Results :The use of mobile apps for drug administration or titration in cases of cardiovascular emergency children has proven to be effective and efficient because it can speed up the preparation time with dose accuracy to minimize ischemia assembled hypotension to vital organs and improve the hemodynamic status and maintain neurological status. Conclusions: Mobile applications is effective and efficient in preventing medical errors in drug administration with the titration method in cases of pediatric cardiopulmonary resuscitation.